Wildberries: Features of Assimilation of a Pseudo-Borrowed Ergonym in Russian - A. M. Dubina; P. I. Kondratenko (Научный диалог, 2025)
This article addresses the assimilation of the proper name ‘Wildberries’ within contemporary Russian. Special attention is given to the status of this name. The authors conclude that ‘Wildberries’ represents a pseudo-borrowed ergonym, as this lexeme is formed as a brand name from English roots, although such a composite does not exist in the English. The relevance of this study is underscored by the rapid pace of borrowing foreign vocabulary, particularly in the context of naming in the Internet domain. The novelty of the research lies in the fact that, for the first time, the phonetic-orthographic, morphological, and communicative-pragmatic features of the assimilation of the ergonym ‘Wildberries’ have been established through a survey of ordinary speakers of Russian. At the phonetic-orthographic level, the study examines the peculiarities of word form representation and identifies instances of hypercorrection when conveying specific aspects of English pronunciation. At the grammatical level, the authors specify the filling of morphological categories of the noun and conclude that these categories have not yet fully stabilized. As for the features of communicative-pragmatic assimilation, the authors highlight linguistic creativity in reinterpreting the name, the use of emotional-evaluative expressions and irony, as well as instances of meta-linguistic reflection among ordinary speakers.